Pendekatan Holistik Dalam Pembelajaran Seni Budaya Tari di Kelas XI IPS 1 SMA Negeri 1 Ulakan Tapakis Kabupaten Padang Pariaman - Rosi Silawati; Susmiarti Susmiarti (Pusat Riset dan Inovasi Nasional, 2023)
The aim of this study is to provide a detailed account of the exhaustive methodology employed in the XI IPS 1 SMA Negeri 1 Ulakan Tapakis course to enhance the learning experience and cultivate students' enthusiasm for the study of dance culture. This investigation is classified as descriptive qualitative research, and its data collection methods include documentation, interviews, and observation. According to the results, the holistic approach utilized in class XI IPS 1 at SMA Negeri 1 Ulakan Tapakis comprised several interdependent elements, such as learning objectives, method selection, and learning media selection, all of which were in accordance with the content or learning material, teachers, and students. These components are intended to foster increased student participation and creativity in the educational process. By promoting students' ability to identify, understand, value, and implement the information presented by the instructor, this methodology guarantees the successful achievement of the Dance Culture educational goals. Class XI IPS 1 SM A N 1 Ulakan Tapakis demonstrates the implementation of a comprehensive approach to dance culture education by employing learning videos, PowerPoint presentation applications, and jigsaw method-based group discussions. Students are not only emotionally stimulated, but also intellectually, sensually, and physically enriched through the implementation of this methodology.